2019
DOI: 10.1097/gox.0000000000002201
|View full text |Cite
|
Sign up to set email alerts
|

Bone Transport Distraction Osteogenesis in the Reconstruction of Pediatric Posttraumatic Calvarial Defects

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…After 8 weeks of extension completion, the mature cortical bone had regenerated, demonstrating the potential application of bone transport techniques in temporo‐mandibular joint reconstruction. In another study, Elbanoby et al 53 . reported the successful reconstruction of large post‐traumatic cranial defects in two young children via BT distraction osteogenesis, yielding satisfactory results.…”
Section: Application Of Bone Transport Technology (Bt) At Atypical Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…After 8 weeks of extension completion, the mature cortical bone had regenerated, demonstrating the potential application of bone transport techniques in temporo‐mandibular joint reconstruction. In another study, Elbanoby et al 53 . reported the successful reconstruction of large post‐traumatic cranial defects in two young children via BT distraction osteogenesis, yielding satisfactory results.…”
Section: Application Of Bone Transport Technology (Bt) At Atypical Sitesmentioning
confidence: 99%
“…After 8 weeks of extension completion, the mature cortical bone had regenerated, demonstrating the potential application of bone transport techniques in temporo-mandibular joint reconstruction. In another study, Elbanoby et al 53 reported the successful reconstruction of large post-traumatic cranial defects in two young children via BT distraction osteogenesis, yielding satisfactory results. Furthermore, Ruben et al 54 described the bone transport DO technique (TDO) for the treatment of mandibular defects after tumor ablation in eight patients with benign tumors, which resulted in successful mandible reconstruction through intraoral BT in all cases.…”
Section: Application Of Bone Transport Technology (Bt) At Atypical Sitesmentioning
confidence: 99%
See 1 more Smart Citation